Diet and Feeding Behavior of the Solpugid, Eremobates Palpisetulosus (Solpugida: Eremobatidae) - Fred Punzo (Psyche: A Journal of Entomology)
Eremobates palipsetulosus is a generalist predator which preys upon a wide variety of arthropods and seems to prefer smaller, soft-bodied prey items. Spiders as welt as orthopteran, lepidopteran and coleopteran insects comprise 76% of the total diet. When a prey item is encountered, the palpi are used to pull the prey toward the chelicerae. The prey is then grasped in the chelicerae which are used to fragment and grind the prey tissues for subsequent ingestion. Increased hunger levels result in significantly faster ingestion time and higher capture rates. This is the first quantitative study on prey capture and feeding behavior for solpugids.